Treatment strategies for neuromyelitis optica - Huang, Tzu-Lun (Tzu Chi Med J, 2018)
Neuromyelitis optica (NMO) is an autoimmune demyelinating disease with pathogenic autoantibodies that act against the astrocyte water channel protein, i.e. aquaporin-4: the disease is associated with recurrent episodes of optic neuritis (ON) and transverse myelitis, often resulting in severe disability. The main goals in treatment of NMO include acute symptomatic therapy and long-term stabilization of symptoms by preventing relapse. In recent years, ongoing randomized controlled trials in NMO patients have studied evidence for treatment. Briefly, acute-stage management (with pulse therapy using corticosteroids and/or plasmapheresis) and maintenance therapy (including rituximab, mycophenolate mofetil, and azathioprine) have been recommended in some case series and retrospective studies. Because of the high prevalence of liver disease, all NMO patients in Taiwan should be screened for hepatitis B and C before treatment is initiated. Although immunosuppression and plasma exchange are the mainstays of therapy for NMO ON, several selective and potentially therapeutic strategies targeting specific steps in NMO pathogenesis including blockers of NMO-IgG binding and inhibitors of granulocyte function have been evaluated in recent years.